2020
DOI: 10.14444/7046
|View full text |Cite
|
Sign up to set email alerts
|

Rational Selection of Patient-Reported Outcomes Measures in Lumbar Spine Surgery Patients

Abstract: Background: The Short Form-12 (SF-12) was developed as a shorter version of the SF-36, yet there has been limited validation of its reliability at measuring postoperative changes. The purpose of this study was to determine if the SF-12 could safely substitute for the SF-36 in measuring postoperative change in lumbar spine surgery patients and if the condition specific (Oswestry Disability Index [ODI]) or pain (visual analog scale [VAS]) instruments, provided additional utility.Methods: A total of 972 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…At 3-years follow-up, their patients had lower ODI scores relative to our patients with a score of 11.68%. Our patient's SF-12 scores can be compared with Cimatti et al 's SF-36 scores, as previous data has shown the SF-12 to be a valid substitute for SF-36 [12]. Cimatti's et al 's [11] patients had lower SF-36 PCS and SF-36 MCS scores at 46 and 56, respectively, relative to our patients' SF-12 scores.…”
Section: Discussionsupporting
confidence: 56%
“…At 3-years follow-up, their patients had lower ODI scores relative to our patients with a score of 11.68%. Our patient's SF-12 scores can be compared with Cimatti et al 's SF-36 scores, as previous data has shown the SF-12 to be a valid substitute for SF-36 [12]. Cimatti's et al 's [11] patients had lower SF-36 PCS and SF-36 MCS scores at 46 and 56, respectively, relative to our patients' SF-12 scores.…”
Section: Discussionsupporting
confidence: 56%
“…The SF-12 questionnaire was chosen as it was proven beneficial in assessing the quality of life of patients in several studies. 12,13 Our data shows that over a mean period of 48 months, 94% (p = 0.009) of the patients who underwent the operation reported relief from biliary pain symptoms. Additionally, there was a positive impact on mental wellbeing and general health.…”
Section: Discussionmentioning
confidence: 73%
“…Our retrospective analysis demonstrates an improvement in the health‐related quality of life symptoms of the patients who underwent LC based on their symptom presentation and HIDA scan results. The SF‐12 questionnaire was chosen as it was proven beneficial in assessing the quality of life of patients in several studies 12,13 . Our data shows that over a mean period of 48 months, 94% ( p = 0.009) of the patients who underwent the operation reported relief from biliary pain symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…Based on the current literature, MCS-12 scores have demonstrated no consistent correlation with improved outcomes after lumbar spine fusion. 27 A previous study found that TKA patients improved markedly less than both THA and LF patients in MCS-12 scores at the 2-year follow-up, although this difference was not present at 1 year postoperatively. 16 Additional evidence exists suggesting that patients with low preoperative MCS-12 scores have markedly greater disability in several other HRQOL scores both at baseline and after LF, although these patients still experience notable postoperative improvement in these domains compared with baseline.…”
Section: Discussionmentioning
confidence: 90%